The relationship of internalized stigma with clinical characteristics and treatment motivation in substance use disorder - Demir, Bahadır; Kocamer Şahin, Şengül; Sancaktar, Muhammet; Sargın, Emine Nur; Köse, Zeynep; Altındağ, Abdurrahman (Journal of Dependence, 2022)
Objective: The aim of this study was to investigate the relationship of internalized stigmatization with treatment motivation and clinical characteristics of patients with substance use disorder (SUD). Method: This research includes 63 participants who were followed up and treated with the diagnosis of substance use disorder in Gaziantep University psychiatry inpatient clinic between June 2020 and December 2020. The socio-demographic data, the scale of internalized stigma in mental illnesses (ISMI) and the treatment motivation questionnaire (TIM) were used to assessment. Results: In correlation analysis; There was no statistically significant relationship between ISMI total and TIM total. Perceived discrimination subscale of ISMI was significantly correlated with the age at onset of substance use. There was a significant differences between patients with and without selfmutilation in terms of stereotype endorsement subscale of the ISMI. There was a significant differences between patients with and without suicide attempt history in terms of stigma resistance subscale of the ISMI. There was no significant correlation between TIM and age at onset of substance use, the number of hospitalizations, the level of education, criminal history, self-mutilation, past suicide attempts, family history of substance use. Conclusion: Although no significant relationship was found between internalized stigmatization and treatment motivation in patients with substance use disorder, it can be concluded that the age of substance onset, self-mutilation, and having history of suicide attempt may affect internalized stigmatization when examined ISMI with the all subscales.